POWER-BANDWIDTH EFFICIENT UPLINK DESIGN FOR INDOOR OPTICAL WIRELESS - SLAIMAN, ISKANDAR YOUNES (2014)
Indoor optical wireless is viable technology which will replace conventional RF communications for high speed network access technologies in the near future. Due to great developments in optoelectronics field, optical wireless communications has gained a lot of advantages over conventional RF communications. Visible light communications which implements illumination systems is the most desirable indoor optical wirelesssystems dueto its cost efficiencyand low complexity.Providinguplink for mobile devices in such these systems is critical issue as multiple factors limits bandwidth and power efficiency. Multipath propagation resulted from user movement degrades achieved bitrate and introduces increased optical power penalty. In this thesis we are reportingon the uplinkin visiblelight communicationsystems as moreavailable bandwidth and lower power consumption are required.